IMPLEMENTASI MANAJEMEN PEMBIAYAAN PADA PRODUK MURABAHAH, MUDHARABAH, DAN MUSYARAKAH DI BANK SYARIAH - Audry Hafifa Listy Biran; Nurhalizah Bandaso; Mhd. Ikhsan Harahap (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study discusses how financing management is applied in Islamic banking, focusing on Murabahah, Mudharabah, and Musyarakah contracts. The research uses a qualitative descriptive approach through literature review, which involves analyzing previous studies, related regulations, and Islamic finance concepts. The study finds that managing financing in Islamic banks is not only about profit optimization but also about ensuring compliance with Sharia values. Each contract requires different strategies for risk control and profit distribution. Effective management helps maintain financial stability, supports the achievement of maqashid Al-Shariah, and strengthens public trust in Islamic financial institutions.